In situ Treatment With Novel Microbiocide Inhibits Methicillin Resistant Staphylococcus aureus in a Murine Wound Infection Model - Hoffmann, Joseph P.; Friedman, Jessica K.; Wang, Yihui; McLachlan, James B.; Sammarco, Mimi C.; Morici, Lisa A.; Roy, Chad J. (Frontiers in Microbiology, 2020)
Increased prevalence of antibiotic resistance in skin and soft tissue infections is a concerning public health challenge currently facing medical science. A combinatory, broad spectrum biocidal antiseptic has been developed (‘ASP’) as a topically-applied solution to potential resistant and polymicrobial infected wounds that may be encountered in this context. The ASP-105 designate was evaluated in vitro by determining the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC), against different strains of methicillin-resistant Staphylococcus aureus (MRSA), resulting estimates of which approximated the positive control (bacitracin). To evaluate in vivo microbicide efficacy, we utilized a murine full thickness wound model to study bacterial infection and wound healing kinetics. Mice were experimentally wounded dorsally and infected with bioluminescent MRSA. The infected wound was splinted, dressed and treated topically with either ASP-105, vehicle (- control), or bacitracin. Bacterial burden and wound healing was monitored using an in vivo imaging system and evaluation of biofilm formation using scanning electron microscopy of wound dressing. Treatment with ASP-105 significantly reduced bacterial burdens in the first three days of infection and inhibited MRSA biofilm formation on the surgical dressing. Notably, treatment with ASP-105 resulted in a sterilizing effect of any detectable MRSA in nearly all (80%; 4/5) of treatment group. All mice receiving vehicle control developed highly MRSA-luminescent and purulent wound beds as a result of experimental infection. The ASP-105 therapy facilitated natural healing in the absence of MRSA infection. Results of this study suggests that that the novel “ASP” combinatory topical antiseptic can be used directly in wounds as a potent, broad-spectrum microbicide against drug resistant S. aureus without injury to the wound bed and impediment of natural restorative processes associated with wound healing. Further studies are warranted to test the effectiveness of this biocidal formulation against other recalcitrant bacterial and fungal pathogens in the context of serious wound infections, and to assess utility of use in both clinical and self-treat scenarios.